Censorship of the American theatre in the twentieth century - Houchin, John H. (Cambridge studies in American theatre and drama, 2003)
John Houchin explores the impact of censorship in twentieth-century American theatre, arguing that theatrical censorship coincided with significant challenges to religious, political and cultural systems. This study provides a summary of theatre censorship in the eighteenth and nineteenth centuries and then analyzes key episodes from 1900 to 2000.